Improved Synthesis and Coordination Behavior of 1H-1,2,3-Triazole-4,5-dithiolates (tazdt2−) with NiII, PdII, PtII and CoIII - Pardemann, Nils; Villinger, Alexander; Seidel, Wolfram W. (Chemistry an international journal, 2023)
A new synthetic route to 1H-1,2,3-triazole-4,5-dithiols (tazdtH2) as ligands for the coordination of NiII, PdII, PtII and CoIII via the dithiolate unit is presented. Different N-protective groups were introduced with the corresponding azide via a click-like copper-catalyzed azide-alkyne [3 + 2] cycloaddition (CuAAC) and fully characterized by NMR spectroscopy. Possible isomers were isolated and an alternative synthetic route was investigated and discussed. After removal of the benzyl protective groups on sulfur by in situ-generated sodium naphthalide, complexes at the [(dppe)M] (M = Ni, Pd, Pt), [(PPh3)2Pt] and [(η5-C5H5)Co] moieties were prepared and structurally characterized by XRD analysis. In this process, the by-products 11 and 12 as monothiolate derivatives were isolated and structurally characterized as well. With regioselective coordination via the dithiolate unit, the electronic influence of different metals or protective groups at N was investigated and compared spectroscopically by means of UV/Vis spectroscopy and cyclic voltammetry. Complex [(η5-C5H5)Co(5c)] (10), is subject to a dimerization equilibrium, which was investigated by temperature-dependent NMR and UV/Vis spectroscopy (solution and solid-state). The thermodynamic parameters of the monomer/dimer equilibrium were derived.